2013
DOI: 10.1158/1078-0432.ccr-13-0312
|View full text |Cite
|
Sign up to set email alerts
|

A Phase I Study of Quisinostat (JNJ-26481585), an Oral Hydroxamate Histone Deacetylase Inhibitor with Evidence of Target Modulation and Antitumor Activity, in Patients with Advanced Solid Tumors

Abstract: Purpose: To determine the maximum-tolerated dose (MTD), dose-limiting toxicities (DLT), and pharmacokinetic and pharmacodynamic profile of quisinostat, a novel hydroxamate, pan-histone deacetylase inhibitor (HDACi).Experimental Design: In this first-in-human phase I study, quisinostat was administered orally, once daily in three weekly cycles to patients with advanced malignancies, using a two-stage accelerated titration design. Three intermittent schedules were subsequently explored: four days on/three days o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
82
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(89 citation statements)
references
References 20 publications
5
82
1
1
Order By: Relevance
“…A phase I clinical trial showed JNJ-26481585 to have a much greater plasma half-life of 8.8 hours in patients with advanced solid tumors compared to other HDAC inhibitors, such as vorinostat and romidepsin (49,50), and it shows promise for use in solid tumors either as a single agent or in combination with SOC (35). The dismal plight of those with advanced NSCLC and the observation here that even early-stage tumors are insensitive to current SOCs highlights the need for novel therapeutic or combinatorial options in this setting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A phase I clinical trial showed JNJ-26481585 to have a much greater plasma half-life of 8.8 hours in patients with advanced solid tumors compared to other HDAC inhibitors, such as vorinostat and romidepsin (49,50), and it shows promise for use in solid tumors either as a single agent or in combination with SOC (35). The dismal plight of those with advanced NSCLC and the observation here that even early-stage tumors are insensitive to current SOCs highlights the need for novel therapeutic or combinatorial options in this setting.…”
Section: Discussionmentioning
confidence: 99%
“…HDAC inhibitors induce apoptosis, cell-cycle arrest, and terminal differentiation in a variety of human tumors and, while currently only clinically licensed for hematological malignancies, show promise in solid tumors, including NSCLC (33). Three class I HDAC inhibitors-JNJ-26481585 (34,35), panobinostat, and vorinostat-were tested in the panel of patient-derived NSCLC specimens. Samples were classified as sensitive, if the IC 50 was below the achievable serum concentrations in humans (1.5 mmol/L panobinostat, 1.81 mmol/L vorinostat: see Supplementary Table S1); as this information was unavailable for JNJ-26481585, 1 mmol/L was arbitrarily set as the cutoff.…”
Section: Hdac Inhibitors Jnj-26481585 and Panobinostat Efficiently Kimentioning
confidence: 99%
“…FGFR1 amplification is considered an adequate factor to predict sensitivity to FGFR inhibitors[24]. However, FGFR inhibitors resulted in insufficient clinical responses in patients with FGFR1- amplified lung cancer[25,26]. A recent study showed that MYC expression might modulate the sensitivity of FGFR1- amplified pulmonary SCC to FGFR1 inhibitors[13].…”
Section: Discussionmentioning
confidence: 99%
“…In estrogen receptor-positive breast cancer, the combination of exemestane with entinostat improves median PFS to 4.3 months and median OS to 28.1 months, whereas median PFS and OS is 2.3 and 19.8 months, respectively, in the exemestane plus placebo group (139). Other HDAC inhibitors, such as ITF2357, CHR-3996, and JNJ-26481585, have been studied and show promising antitumor effect (140)(141)(142).…”
Section: Hdac Inhibitorsmentioning
confidence: 99%